Exosomal PD-L1 in cancer and other fields: recent advances and perspectives - Lu, Man-Man; Yang, Yu (Frontiers in Immunology, 2024)
PD-1/PD-L1 signaling is a key factor of local immunosuppression in the tumor microenvironment. Immune checkpoint inhibitors targeting PD-1/PD-L1 signaling have achieved tremendous success in clinic. However, several types of cancer are particularly refractory to the anti–PD-1/PD-L1 treatment. Recently, a series of studies reported that IFN-γ can stimulate cancer cells to release exosomal PD-L1 (exoPD-L1), which possesses the ability to suppress anticancer immune responses and is associated with anti-PD-1 response. In this review, we introduce the PD-1/PD-L1 signaling, including the so-called ‘reverse signaling’. Furthermore, we summarize the immune treatments of cancers and pay more attention to immune checkpoint inhibitors targeting PD-1/PD-L1 signaling. Additionally, we review the action mechanisms and regulation of exoPD-L1. We also introduce the function of exoPD-L1 as biomarkers. Finally, we review the methods for analyzing and quantifying exoPD-L1, the therapeutic strategies targeting exoPD-L1 to enhance immunotherapy and the roles of exoPD-L1 beyond cancer. This comprehensive review delves into recent advances of exoPD-L1 and all these findings suggest that exoPD-L1 plays an important role in both cancer and other fields.